Pavel Bermondt-Avalov and the Formation of the West Russian Volunteer Army – Warlordism in the Baltic? - Rettig, Thomas (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2021)
Warlordism is a phenomenon that emerges in a power vacuum during wars, civil wars and revolutions. There are many examples from the Russian Civil War where military commanders amassed absolute power in certain areas, without being subordinate to any state authority, or perhaps being subordinate in name only. Pavel Bermondt-Avalov, who formed the West Russian Volunteer Army, is discussed as an example of a warlord from the era of the Baltic wars of independence. A large portion of his army was made up of the German soldiers and officers who, as members of Freikorps, had fought in the Iron Division under the command of General Rüdiger von der Goltz, or in other units in the first half of 1919. In the autumn of 1919, instead of fighting the Bolsheviks and the Red Army, he turned his weapons against the Republic of Latvia and marched on Riga.